Influence strategies and organisational success - Tripathi, Sangeeta; Tripathi, Nachiketa (2001)
The present paper makes an attempt to investigate the relationship between Downward Influence Strategies and Organisational Success, which includes Job Satisfaction (JS), Effectiveness (EFF) and Intention to Quit (IQ). This study is based on a sample of 200 middle level executives of 10 public and private sector organisations. The findings indicate that less use of Asserting Expertise and Negative Sanction and frequent use of Rational Rewards and Personalized Relationship would enhance the JS, and EFF is also likely to be enhanced by the use of Rational Rewards. Asserting Expertise may increase Intention to Quit the organisation. - Reproduced
Keywords: Job satisfaction; Managers; Organizations